Late Quaternary hydrological change from fluvial archives in southwestern Africa and the palaeoclimate implications - Walsh, EV (2022)
Fluvial sedimentary sequences provide important archives of late Quaternary palaeoenvironmental change. In drylands, these stores of information in fluvial landforms can be found in regions that are commonly scarce in long-term palaeoproxy records due to low levels of precipitation and poor organic preservation. In southwestern Africa, proposed drivers of Quaternary climate change carry with them a suite of hypotheses with respect to patterns of precipitation variability, yet poor coverage of palaeoclimate archives has to date made it challenging to assess model-based predictions. Here, fluvial archives offer the potential to provide the spatial and temporal coverage of palaeorecords that is required. Whilst it is well-established that dryland fluvial systems respond to hydroclimate changes on Quaternary timescales, deciphering the palaeoenvironmental histories they preserve is often complex. To date, the utility of records from fluvial archives in southwestern Africa has been hindered by low-resolution chronologies, limited use of robust methods to interrogate the context of sediment deposition, and a focus on individual studies with limited consideration of regional controls.